Mid‐term clinical outcomes from use of Sirolimus coated balloon in coronary intervention; data from real world population. Issue 1 (30th May 2020) - Basavarajaiah, Sandeep; Athukorala, Sampath; Kalogeras, Konstantinos; Panoulas, Vasileios; Loku Waduge, Bhagya H.; Bhatia, Gurbir; Watkin, Richard; Pulikal, George; Lee, Kaeng; Ment, Jerome; Freestone, Bethan; Pitt, Michael
Abstract: Background: Use of drug coated balloons (DCBs) in coronary intervention is escalating. There is a plethora of data on Paclitaxcel‐DCB. However, when it comes of stents, Limus‐drugs are preferred over Paclitaxel. There is very limited data on Sirolimus coated balloons (SCB). MagicTouch‐SCB (Concept Medical, FL) elutes Sirolimus via nano‐technology and have been used in our centers since March 2018. We report a mid‐term follow‐up with this relatively novel‐technology. Methods and results: We retrospectively analyzed all patients treated with MagicTouch‐SCB between March‐2018 and February‐2019. Results are reported as cardiac‐death, target‐vessel myocardial‐infarction (TVMI), target lesion revascularization (TLR) and Major Adverse Cardiac Events (MACE). During the study period, 288‐patients (373‐lesions) with a mean age of 65.8 were treated with MagicTouch‐SCB. 84% ( n = 241) were male, 155 (54%) were in the setting of acute coronary syndrome, 38% ( n = 110) had diabetes and 62% ( n = 233) were in de‐novo lesions. Most lesions treated were in the LAD/diagonal‐system ( n = 170; 46%). Pre‐dilatation was performed in 92% ( n = 345) of cases. Bailout stenting was required in 9% lesions ( n = 35). The mean diameter and length of SCBs were 2.64 ± 0.56 mm and 24 ± 8.9 mm respectively. During a median follow‐up of 363 days (IQR: 278–435), cardiac death and TVMI occurred in 5‐patients (1.7%) and 10‐patients (3.4%) respectively, TLR per‐lesion was 12%. The MACE rate was 10%. There were no documented cases of acute vessel closure. Conclusions: The results from mid‐term follow‐up with this relatively new technology SCB is encouraging with a low rates of hard endpoints and acceptable MACE rates despite complex group of patients and lesion subsets.